2022
DOI: 10.3390/ijms23158366
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy Machinery in Magnaporthe oryzae

Abstract: Plant diseases cause substantial loss to crops all over the world, reducing the quality and quantity of agricultural goods significantly. One of the world's most damaging plant diseases, rice blast poses a substantial threat to global food security. Magnaporthe oryzae causes rice blast disease, which challenges world food security by causing substantial damage in rice production annually. Autophagy is an evolutionarily conserved breakdown and recycling system in eukaryotes that regulate homeostasis, stress ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 95 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…TOR adjusts cellular functions based on nutrient availability: suppressing autophagy when nutrients are plentiful but triggering cellular degradation via autophagosomes when nutrients are scarce or TOR is inhibited by rapamycin. Studying its role in plant-infecting fungi may aid in the avoidance and healing of rice blast disease [16]. MoLst8 is a crucial component of the TOR complex, and our research has found that the absence of MoLST8 impairs TOR and autophagy.…”
Section: Discussionmentioning
confidence: 91%
“…TOR adjusts cellular functions based on nutrient availability: suppressing autophagy when nutrients are plentiful but triggering cellular degradation via autophagosomes when nutrients are scarce or TOR is inhibited by rapamycin. Studying its role in plant-infecting fungi may aid in the avoidance and healing of rice blast disease [16]. MoLst8 is a crucial component of the TOR complex, and our research has found that the absence of MoLST8 impairs TOR and autophagy.…”
Section: Discussionmentioning
confidence: 91%
“…M. oryzae activates autophagy to counter host-imposed stress and facilitate infection ( 25 , 56 , 57 ). In yeast and mammalian cells, Atg1 is the conserved protein kinase that phosphorylates Atg9 to positively regulate autophagy ( 47 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagosomes are double-membrane structures formed by the phagophores sequestering cytoplasmic elements ( 25 ). Their formation involves a highly regulated and continuous membrane fusion process, including the generation of autophagosomal membrane precursors and phagophore elongation ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy leads to the encapsulation of excess or damaged proteins or organelles in the cytoplasm into vesicles that fuse with lysosomes to form autolysosomes, which degrade their encapsulated contents [ 74 , 75 ]. This process is beneficial for cells to renew their organelles and prevent further impairment by damaged organelles.…”
Section: Molecular Mechanism Of If Alleviation Of Dn Progressionmentioning
confidence: 99%